Branding dan Digital Marketing dalam Optimalisasi Laba dan Financial Sustainability UMKM - Rohma Septiawati; Rivan Wibowo; Fista Apriani Sujaya; Mumun Maemunah; Moch Agus Ariffianto; Abdul Husenudin (Masyarakat Ekonomi Syariah Bogor, 2026)
This study aims to analyze the role of branding and digital marketing in optimizing profit and financial sustainability of Jamu Bu Bekti MSME in Karawang. This research uses a qualitative approach with observation and interview methods with the business owner. The results show that branding builds business identity and consumer trust, leading to increased sales. Digital marketing expands market reach and enhances customer engagement, thereby increasing revenue. The combination of both contributes to profit growth that supports the long-term financial sustainability of MSMEs. Therefore, branding and digital marketing are important factors in strengthening MSME competitiveness in the digital era.